2013
DOI: 10.1088/0031-9155/58/12/4071
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation editing improves efficiency while reducing inter-expert variation and maintaining accuracy for normal brain tissues in the presence of space-occupying lesions

Abstract: Image segmentation has become a vital and often rate limiting step in modern radiotherapy treatment planning. In recent years the pace and scope of algorithm development, and even introduction into the clinic, have far exceeded evaluative studies. In this work we build upon our previous evaluation of a registration driven segmentation algorithm in the context of 8 expert raters and 20 patients who underwent radiotherapy for large space-occupying tumors in the brain. In this work we tested four hypotheses conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“… 8 Using atlas-based registration to segment the eyes and the brain stem and the atlas-navigated optimal medial axis and deformable model algorithm for other structures followed by manual editing, they then showed in another study that it could reduce interobserver variation, improve accuracy, and reduce segmentation time by about 60%. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Using atlas-based registration to segment the eyes and the brain stem and the atlas-navigated optimal medial axis and deformable model algorithm for other structures followed by manual editing, they then showed in another study that it could reduce interobserver variation, improve accuracy, and reduce segmentation time by about 60%. 9 …”
Section: Discussionmentioning
confidence: 99%
“…If automated segmentation alone was accurate, this could reduce segmentation time. However, the physician is still needed to further segment structures, 4 , 9 especially in the context of inverse-planned hypofractionated radiation therapy. Using both an automated software and manual editing may be the current best of both worlds to deliver safe treatment to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported failures of individual expert rater segmentations because structural MRI may obscure the precise visual delineation of glioma boundaries [10] [12] . In addition, manual segmentation is time-consuming and is a rate-determining step for further treatment planning [13] . Fully automated user-independent segmentation tools are available for research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported failures of individual expert rater segmentations because structural MRI may obscure the precise visual delineation of glioma boundaries [10][11][12]. In addition, manual segmentation is time-consuming and is a rate-determining step for further treatment planning [13]. Fully automated user-independent segmentation tools are available for research purposes.…”
Section: Introductionmentioning
confidence: 99%